Introducing Trinity and avoiding Trimūrti: The reception of the Trinitarian doctrine of the Nicene-Constantinopolitan Creed in Early Modern India - Aranha, Paolo (Concilium, 2025)
Striking similarities between Christianity and Hinduism were noticed by Europeans since the early modern time, and are confirmed even by today's religious practice. Since the sixteenth century missionaries believed that the Christian Trinity and the Hindu Trimūrti of Brahmā, Viṣṇu and Śiva might be somehow related. This article presents various interpretations that were given for such a supposed analogy, hence assuming that the Trimūrti was either a relic or a prefiguration of Christianity, or alternatively a diabolic mockery of it. Furthermore, the article shows how a ritual object with a ternary structure hinting at Trimūrti was resignified so as to indicate Trinity.